2008
DOI: 10.4103/1817-1737.39676
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between high-resolution computed tomography features and patients′ characteristics in chronic obstructive pulmonary disease

Abstract: BACKGROUND:During the last few decades, high-resolution computed tomography (HRCT) has come up as a new diagnostic modality to diagnose emphysematous and chronic bronchitis components of chronic obstructive pulmonary disease (COPD). The present study was undertaken to evaluate for various quantitative and qualitative HRCT features in patients with COPD, and to detect patients' characteristics that correlate with these HRCT features.MATERIALS AND METHODS:Forty male patients with COPD attending the COPD clinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 24 publications
3
37
2
Order By: Relevance
“…Indeed, the degree of tracheal collapse at end expiration in patients with COPD does not appear to be significantly different from that of control subjects (121). However, narrowing of the trachea in the coronal plane (saber-sheath trachea) is associated with COPD-particularly with more advanced stages of COPD (121)(122)(123). Diverticula or outpouching from the central airways may also be present; although the prevalence of bronchial diverticula is not different in patients with COPD than in control subjects (124), an increased number of diverticula is associated with a history of cigarette smoking (125) and with symptoms of cough (126).…”
Section: Abnormalities Of the Trachea And Central Bronchimentioning
confidence: 99%
“…Indeed, the degree of tracheal collapse at end expiration in patients with COPD does not appear to be significantly different from that of control subjects (121). However, narrowing of the trachea in the coronal plane (saber-sheath trachea) is associated with COPD-particularly with more advanced stages of COPD (121)(122)(123). Diverticula or outpouching from the central airways may also be present; although the prevalence of bronchial diverticula is not different in patients with COPD than in control subjects (124), an increased number of diverticula is associated with a history of cigarette smoking (125) and with symptoms of cough (126).…”
Section: Abnormalities Of the Trachea And Central Bronchimentioning
confidence: 99%
“…Patients with COPD often suffer from bronchitis-like symptoms and most patients also have pathophysiological changes in the lung that are associated with emphysema. 4 The availability of several treatment guidelines has provided physicians with different definitions of COPD in which post-bronchodilator obstruction plays a pivotal role. 1,5 However, a clinical diagnosis of COPD also includes a history of smoking and/or exposure to risk factors such as pollutants or occupational dusts.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was found that mosaic attenuation pattern in addition to other HRCT features is helpful in distinguishing different entities grouped under COPD (Copley et al 2002). In our studies (Gupta et al 2008(Gupta et al , 2009) including 40 COPD patients who were diagnosed based on GOLD criteria and who were evaluted for HRCT characteristics, 16/40 patients had classic mosaic attenuation pattern; the HRCT scans were undertaken during full inspiration. Some of these are shown in figure 1 (A to F).…”
Section: Mosaic Attenuation Pattern and Air Trappingmentioning
confidence: 99%
“…Since then, HRCT has been widely established to detect and quantify COPD and its subtypes. Several workers have studied the correlation of semi-quantitative scoring of COPD by HRCT, pathology, clinical features and pulmonary function tests (Sanders et al 1988;Gupta et al 2008Gupta et al , 2009). HRCT indices of emphysema reflect lung anatomy and represent the best way to assess emphysema severity in life (Newell et al 2004).…”
Section: High Resolution Computed Tomography: Evolution With the Timementioning
confidence: 99%